PERLINDUNGAN HUKUM TERHADAP PENGGUNA JASA TERKAIT LARANGAN MEMBAWA MAKANAN & MINUMAN DARI LUAR (Studi Pada Wahana Hiburan Anak di Kota Pontianak) - NIM. A1011181068, ISMIYAH KHAIRANI (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT The business of children's amusement rides is increasingly being established in various parts of Indonesia, especially in big cities. In Pontianak City itself there are various kinds of children's amusement rides. This potential market is used by business actors for children's amusement rides to compete in providing their best offers through their children's amusement rides business. Without us realizing it, these business actors have harmed us as consumers. In running a business, business actors are required to maintain a balance between consumers and the business actors themselves, so that consumer rights are not ignored or even eliminated in the process of enjoying the services of the children's amusement rides. However, in practice, almost all children's amusement rides businesses in Pontianak City have violated consumer rights, one of which is the inclusion of the